Network-forming phase separation of oppositely charged polyelectrolytes forming coacervates in a solvent - Jiaxing Yuan; Hajime Tanaka (Nature Communications)
Abstract The formation of coacervates through phase separation of oppositely charged polyelectrolytes (PEs) is critical for understanding biological condensates and developing responsive materials. Traditionally, coacervates are viewed as spherical droplets with growth dynamics resembling liquid-liquid phase separation. However, our fluid particle dynamics simulations incorporating hydrodynamic and electrostatic interactions challenge this perspective. Here, we find that oppositely charged PEs form a percolated network even in semi-dilute solutions, coarsening with a unique growth law, ℓ ∝ t 1/2. This self-similarity, absent for neutral polymers in poor solvents, arises because PEs in good solvents exhibit weaker, longer-range attractions due to spatial charge inhomogeneity under global charge neutrality. This results in a lower density of the PEs-rich phase and reduced interfacial tension. Increased charge asymmetry further slows network coarsening. Additionally, coacervate droplets initially display irregular shapes due to weak interfacial tension, transitioning slowly to spherical forms. Our research provides new insights into coacervate morphology and coarsening dynamics.